2021
DOI: 10.1111/ics.12754
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive skin: Active ingredients on the spotlight

Abstract: Objective Sensitive skin is characterized by self‐reported sensory perceptions in response to stimuli that should not provoke unpleasant sensations. Cosmetic products for sensitive skin are designed to minimize these symptoms. This study aimed to unveil the most used active ingredients for sensitive skin in facial care products from the pharmacy and parapharmacy channel. Methods A pool of products from the pharmacy and parapharmacy channel whose label included the expressions ‘sensitive skin’, ‘reactive skin’ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 93 publications
0
18
0
Order By: Relevance
“…Allantoin is often used to soothe dry, irritated skin due to its anti‐inflammatory, keratolytic and moisturising (i.e. emollient) properties 89 . In vivo studies have also demonstrated allantoin's potential in wound healing 89,90 .…”
Section: Allantoinmentioning
confidence: 99%
“…Allantoin is often used to soothe dry, irritated skin due to its anti‐inflammatory, keratolytic and moisturising (i.e. emollient) properties 89 . In vivo studies have also demonstrated allantoin's potential in wound healing 89,90 .…”
Section: Allantoinmentioning
confidence: 99%
“…, promotes lipid synthesis, fibroblast proliferation, and wound healing, has anti-inflammatory and anti-pruritic roles, fights against stress-induced radicals, etc. ), being highly convenient for sensitive skin health treatments. …”
Section: Introductionmentioning
confidence: 99%
“…Among its many skin care benefits can be mentioned the reduction of skin irritation, anti-inflammatory properties and wound healing properties [ 23 , 24 ]. Numerous clinical studies have shown that allantoin has both a moisturizing effect and a strong stimulation of cell proliferation and tissue regeneration [ 25 , 26 ]. The beneficial characteristics of this bioactive compound justify its utility and applications in numerous compositions formulated for the cosmetic industry, for the treatment of chronic wounds such as ulcers or for the healing of injuries, wounds and burns [ 27 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%